An agrarian history of South Asia - Ludden, David E. (Cambridge University Press, 1999)
David Ludden's book offers a comprehensive historical framework for understanding the regional diversity of agrarian South Asia. Adopting a long-term view of history, it treats South Asia not as a single civilization territory, but rather as a patchwork of agrarian regions, each with their own social, cultural and political histories. The discussion begins during the first millennium, when farming communities displaced pastoral and tribal groups and goes on to consider the development of territoriality from the sixteenth to nineteenth century. Subsequent chapters consider the emergence of agrarian capitalism in village societies under the British, and demonstrate how economic development in contemporary South Asia continues to reflect the influence of agrarian localism. As a comparative synthesis of the literature on agrarian regimes in South Asia, the book promises to be a valuable resource for students of agrarian and regional history as well as of comparative world history.
Keywords: Agriculture -- Economic aspects -- India.; Agriculture -- India -- History.; Agriculture -- Aspect économique -- Inde.; Agriculture -- Inde -- Histoire.; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science.; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General.; Agriculture; Agriculture -- Economic aspects; India; Landbouw.; Zuid-Azië.; Humaniora -- Historie.; History